2021
DOI: 10.1002/ajh.26378
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy for primary immune thrombocytopenia revisited in the era of thrombopoietin receptor agonists: New insights for an old treatment

Abstract: Although splenectomy is still considered the most effective curative treatment for immune thrombocytopenia (ITP), its use has significantly declined in the last decade, especially since the approval of thrombopoietin receptor agonists (TPO-RAs).The main objective of the study was to determine whether splenectomy was still as effective nowadays, particularly for patients with failure to respond to TPO-RAs.Our secondary objective was to assess, among patients who relapsed after

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 24 publications
4
42
3
1
Order By: Relevance
“…Some treatment options for ITP are costly and require long-term treatment, others are less expensive but have significant side effects. Splenectomy is considered to be the effective treatment for ITP, however prospective studies 5 have shown that with the advent of newer second-line therapy drugs such as thrombopoietin receptor agonist (TPO-RA), the clinical use rate of splenectomy for ITP is gradually decreased. 6 Nazy et al 7 have found that TPO and TPO receptor (C-MPL) autoantibodies were detectable in 44% of patients with ITP and other thrombocytopenic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Some treatment options for ITP are costly and require long-term treatment, others are less expensive but have significant side effects. Splenectomy is considered to be the effective treatment for ITP, however prospective studies 5 have shown that with the advent of newer second-line therapy drugs such as thrombopoietin receptor agonist (TPO-RA), the clinical use rate of splenectomy for ITP is gradually decreased. 6 Nazy et al 7 have found that TPO and TPO receptor (C-MPL) autoantibodies were detectable in 44% of patients with ITP and other thrombocytopenic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This leaves splenectomy which is remarkably effective; recent work suggests that it remains effective even in patients who have been treated with thrombopoietin agents. 48 Why are patients so unwilling to undergo splenectomy? Perhaps the primary reasons are the inability to know whether a patient will get better on their own, whether the splenectomy will be successful, and the irreversibility of it.…”
Section: Discussionmentioning
confidence: 99%
“…Late relapse beyond 2 years after splenectomy is very uncommon. Whether delaying splenectomy reduces its efficacy is a concern; a recent study from France 48 suggests that efficacy is maintained, and some patients responded better to TPO-RA after splenectomy.…”
Section: Section I a Young Female Patient With Immune Thrombocytopeni...mentioning
confidence: 99%
“…Splenectomy remains the most effective therapy for corticosteroid-resistant or relapsed ITP patients by removing the major site of platelet phagocytosis and autoantibody production. Although splenectomy is becoming less preferred nowadays due to the availability of emerging non-surgical medications, it still offers the best chance for long-lasting remission, with an estimated durable response rate of 60–70% [ 148 ], even in TPO-RA and/or rituximab-resistant or relapsed patients [ 149 ]. There is also evidence that even though CR was not achieved after splenectomy, most patients displayed a milder course of the disease and responded better to medical treatment [ 149 , 150 ].…”
Section: Subsequent Treatmentmentioning
confidence: 99%
“…Although splenectomy is becoming less preferred nowadays due to the availability of emerging non-surgical medications, it still offers the best chance for long-lasting remission, with an estimated durable response rate of 60–70% [ 148 ], even in TPO-RA and/or rituximab-resistant or relapsed patients [ 149 ]. There is also evidence that even though CR was not achieved after splenectomy, most patients displayed a milder course of the disease and responded better to medical treatment [ 149 , 150 ]. Most guidelines recommend deferring splenectomy for 12–24 months after diagnosis as some patients have a chance of spontaneous remission or stabilization of platelet count at a hemostatic level [ 11 , 12 ].…”
Section: Subsequent Treatmentmentioning
confidence: 99%